Халхын толгой баяны нэг Сүрэн гавьж - Болдбаатар, Жигжид; Пүрэвсүрэн, Ц. (Historia Mongolarum, 2006)
XX зууны эхэн үеийн Монголын язгуур угсаагүй шинэ баячуудын нэг П.Сүрэнгийн аж ахуйгаа хөтлөх арга ухаан, бэл бэнчин, хүний мөс чанарын тухай өгүүлнэ. P.Suren was a representative of the newly emerging bourgeoisie in Mongolia at the onset of the 20th century. He was a legendary figure, a wealthy man known for his managerial skills and human touch for others. His life was unfortunately abrupt during the Reign of Terror in 1938.